STRENGTHENING THE QUALITY ASSURANCE SYSTEM THROUGH TRACER STUDIES: AN EVIDENCE-BASED QUALITY ASSURANCE PERSPECTIVE - Anila Umriana (PT. Media Akademik Publisher, 2026)
Tracer studies are strategic instruments in higher education quality assurance systems because they provide relevant graduate outcome data for evidence-based decision making. This study aims to analyze the implementation and utilization of tracer studies in the Internal Quality Assurance System (SPMI) at UIN Walisongo Semarang from the perspective of evidence-based quality assurance. This study uses a qualitative approach with a case study design. Data were collected through in-depth interviews, documentation studies, and limited observations, then analyzed using the Miles and Huberman interactive model. The results show that the tracer study at UIN Walisongo has a clear policy basis and is implemented based on technical guidelines integrated into the SPMI. Tracer study data is mainly used in the evaluation and improvement stages of the PPEPP cycle, particularly to assess the relevance of the curriculum and the competency achievements of graduates. However, the utilization of tracer study results is not yet optimal because it is still limited to reporting and has not been consistently followed up in quality improvement planning. This study recommends strengthening the integration of tracer studies in all stages of PPEPP, strengthening cross-unit governance, and developing a culture of quality so that tracer studies function effectively as an evidence-based quality assurance instrument in higher education.